Solubility Studies of Haloglycine by Quantum Mechanical Method - Sampath Krishnan, S.; Balamurugan, N.; Kumutha, R.; Mahalakshmi, S. (Asian Journal of Chemistry, 2012)
Quantum mechanical solvation analysis account for electric and electro static components of solvation by microscopic surface tension. The polarizable continuum solvation model (PSCM) is extended to the compounds of haloglycine. The free energy of solvation of the compounds is discussed. The effects of dispersion energy, repulsion energy are calculated. The dipole moments and cavities are calculated and discussed.